Fixed Point Theorems in Complete Partial G-Metric Spaces for Generalized Contractive Conditions of the Cyclical Type - Ampadu, Clement Boateng (Journal of Global Research in Mathematical Archives(JGRMA), 2014)
This paper proves some fixed point theorems for generalized contractions defined on cyclic representation in the setting of partial G-metric spaces.